Sovereigns of the Sea: The Quest to Build the Perfect Renaissance Battleship - Koristam Angus (Wiley, 2008)
It was the age of the great humanist scholars,of poets, architects, painters, inventors,scientists, sculptors, and doctors—and of oneof the most ferocious and costly arms racesin history. Beginning with the first marriage of guns and ships in the early fifteenth century,the monarchs of Europe launched a desperate competition to rule the waves with ever larger, more powerful, and more seaworthy warships. Driven by continuous advances in gunfounding technology, this deadly contest gave rise, almost immediately, to national navies, led to greatleaps in shipbuilding and design, and produced revolutions in naval strategy and tactics. The price of these advances was always enormous and, in some cases, ruinous.